PERAN GURU DALAM MENGEMBANGKAN KARAKTER BERSAHABAT/KOMUNIKATIF SISWA PADA KELAS IX DI SMP NEGERI 7 BANJARMASIN - Alvira, Theresia; Agus Ruchliyadi, Dian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A friendly/communicative character is important in fostering harmonious and inclusive social relationships at school. However, in reality, the issues in this study indicate that the friendly/communicative character of ninth-grade students at SMP Negeri 7 Banjarmasin is still relatively low, especially in social interactions between diverse students, including children with special needs. This is evident in a lack of empathy, impolite communication, and a low level of acceptance of differences. This study aims to describe the role of teachers in developing a friendly/communicative character and the obstacles encountered in this process. This study used a descriptive qualitative method. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results show that: (1) the role of teachers in developing a friendly/communicative character is as facilitators, role models, and motivators. Teachers as facilitators create active and interactive learning and provide opportunities for students to communicate and collaborate. As role models, teachers demonstrate a friendly attitude, respect for differences, and good communication. As motivators, teachers provide encouragement and guidance to foster empathy, cooperation, and positive communication. Character development is also carried out through learning and co-curricular activities. (2) Obstacles encountered include social jealousy and envy among students, barriers to interaction with students with special needs, a tendency to form friendship groups (circles) and introverted behavior, and poor social etiquette among students. It is recommended that schools and teachers continue to enhance their roles in creating an inclusive, harmonious, and diversity-respecting environment.